Procedure-Related Complications after Genetic Amniocentesis and Chorionic Villus Sampling - Kollmann, M.; Haeusler, M.; Haas, J.; Csapo, B.; Lang, U.; Klaritsch, P. (Ultraschall in der Medizin - European Journal of Ultrasound, 2013)
Purpose: Amniocentesis (AC) and chorionic villus sampling (CVS) play an important role in the diagnosis of genetic anomalies. The aim of this study was to evaluate presentable numbers of procedure-related complications of genetic interventions in a tertiary referral hospital. Materials and Methods: The pregnancy outcome of women who underwent genetic AC or CVS during 2003 – 2010 at the Department of Obstetrics and Gynecology, Medical University of Graz, Austria, was analyzed retrospectively. The primary outcome was miscarriage or membrane rupture after an invasive procedure. Only singleton gestations were included. Results: 1,569 AC procedures and 334 CVS procedures (234 transabdominal, 99 transcervical, 1 with undocumented route) were performed. Of these, 57 cases were excluded from further analysis because of severe anomalies. Complete outcome data were available for 93.17 % of cases. In 164 (8.89 %) cases the pregnancy was terminated due to genetic anomalies or severe malformations. In the remaining collective 10 of 1,342 (0.75 %) AC procedures, 3 of 150 (2.00 %) transabdominal CVS procedures and 2 of 64 (3.13 %) transcervical CVS procedures lead to complications resulting in miscarriage < 24 weeks (n = 13) or rupture of membranes (n = 2) within 2 weeks after procedure. Complication rates were significantly higher after CVS than after AC (OR 3.19). Conclusion: Over an observation period of seven years, the complication rates after AC, transabdominal CVS and transcervical CVS were 0.75 %, 2.00 % and 3.13 %, respectively. These results are comparable to recent international investigations.
Keywords: obstetrcis; pregnancy; amniocentesis; chorionic villus; sampling